2015
DOI: 10.1007/s40751-015-0004-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving Grade 7 Students’ Achievement in Initial Algebra Through a Technology-Based Intervention

Abstract: Digital technology plays an increasingly important role in daily life, mathematics education and algebra education in particular. To investigate the effect of a technology-rich intervention related to initial algebra on the achievement of 12-13 year old Indonesian students, we set up an experiment. The experimental group's intervention focused on equations in one variable and is characterized by an alternated use of paper-and-pencil and digital work, and by the intertwining of word problems and bare algebra pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…The duration of an activity was addressed by Jupri, Drijvers, and Van Den Heuvel-Panhuizen (2015). In their case, the intervention lasted for more than 5 h. However, the students in their study did not use a duo of artifacts but either a digital or a physical artifact.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of an activity was addressed by Jupri, Drijvers, and Van Den Heuvel-Panhuizen (2015). In their case, the intervention lasted for more than 5 h. However, the students in their study did not use a duo of artifacts but either a digital or a physical artifact.…”
Section: Discussionmentioning
confidence: 99%
“…Students who have reached the middle grades and are still experiencing difficulty with mathematical concepts are often provided with rote approaches only, keeping them from gaining the conceptual frameworks necessary for success with algebraic tasks (Dacey & Gartland, 2019). One of the interventions to deal with these students" difficulty is by supporting it with digital manipulative and helping students expand brackets (Jupri, Drijvers, & van den Heuvel-Panhuizen, 2015).…”
Section: Examplementioning
confidence: 99%
“…The role ranges from learning management (Hoyos, 2012) to implementing online assessments or tests (Drijvers et al, 2014). Many studies have shown that teachers and students have a positive attitude toward using digital technology in education (Afify, 2019;Drijvers et al, 2014;Jupri, Drijvers, and van den Heuvel-Panhuizen, 2015;Putra, Witri, and Yulita, 2019). The exploitation of technology for online assessment, when used effectively, can be particularly valuable in the assessment of 21 st -century learning (Boitshwarelo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%